SPIRITUAL RELIGIUS SEBAGAI BASIS ETIKA AKUNTAN PROFESIONAL - Ida Ayu Nursanty (Valid: Jurnal Ilmiah, 2016)
This research aims to make spiritual-religious ethics as a basis of professional accountants. This study uses a spiritualist paradigm (spiritual paradigm) and the design of this study spiritualist (spiritualist research design). Through the method of prayer, tafakkur, and dhikr, researchers gain inspiration consciousness Tawheed as the research methodology. The data used is secondary data obtained in a rational and intuitive. The results of this study indicate that religious-spiritual that has been imprinted in themselves an accountant, can provide a creative spirit for accountants goes beyond professional tasks that allow accountants to find solutions in the stalled situation. Instead accountants who have a low spirituality tends to perform unethical behaviour in their work as a professional. This suggests that accountants can not serve the public good and not be inspired to provide creative solutions on matters of urgency